Alternative jet fuels: challenges and prospects - Яновский, Л.С.; Федоров, Е.П.; Варламова, Н.И.; Бородако, П.В.; Попов, И.М. (Proceedings of National Aviation University (archive), 2009)
In the article basic problems and prospects of the use of fuels are considered for ramjets. Basic technologies of receipt of alternative reactive fuels are described.